2011
DOI: 10.1007/s10802-011-9517-3
|View full text |Cite
|
Sign up to set email alerts
|

Friendship as Protection from Peer Victimization for Girls with and without ADHD

Abstract: The goal of this study was to examine the ability of friendship to moderate the association between behavioral risk and peer victimization for girls with attention-deficit/hyperactivity disorder (ADHD; n = 140) and comparison girls (n = 88) in a 5-week naturalistic summer camp setting. Participants were an ethnically and socioeconomically diverse group of girls ages 6-12. Parents and teachers reported on pre-summer internalizing behavior, externalizing behavior, and social competence. Participants reported on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 41 publications
1
55
1
3
Order By: Relevance
“…Across three separate experiments with different groups of participants drawn from different schools, we have provided robust evidence that a victim reputation may precede being eschewed as a friend/buddy. It is noteworthy that other studies have reported that associations between a range of risk factors and victimization across time may be attenuated by the presence of good relationships, especially friendship (Cardoos & Hinshaw, 2011;Fox & Boulton, 2006;Hodges et al, 1999). However, this kind of data only indirectly implicates good peer relationships as coming before victimization because they focused on peer relationships as moderators rather than predictors of victimization.…”
Section: General Discussion Limitations and Implicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Across three separate experiments with different groups of participants drawn from different schools, we have provided robust evidence that a victim reputation may precede being eschewed as a friend/buddy. It is noteworthy that other studies have reported that associations between a range of risk factors and victimization across time may be attenuated by the presence of good relationships, especially friendship (Cardoos & Hinshaw, 2011;Fox & Boulton, 2006;Hodges et al, 1999). However, this kind of data only indirectly implicates good peer relationships as coming before victimization because they focused on peer relationships as moderators rather than predictors of victimization.…”
Section: General Discussion Limitations and Implicationsmentioning
confidence: 87%
“…One is based on the substantial evidence that friendships are central areas of concern to early adolescents and affect their well-being (Bukowski, Newcomb, & Hartup, 1998;Hartup, 1996). The other is that friendships offer some protection against victimization (Boulton et al, 1999;Cardoos & Hinshaw, 2011;Hodges et al, 1997Hodges et al, , 1999Kochenderfer & Ladd, 1997;Pellegrini et al, 1999;Perry et al, 1988). Clearly, it is important to find out more about the links between victimization and friendship formation.…”
Section: Social Relationships Of Victims Of Bullying and Directions Omentioning
confidence: 99%
“…Cardoos and Hinshaw [65], using the same summercamp data as Blachman and Hinshaw [64], investigated whether friendship participation could act as a buffer for peer victimisation. They reported that girls with ADHD had significantly lower rates of friendship participation relative to TD girls (Cohen’s d = 0.31).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies in samples of children with externalizing behavior or ADHD have found that having at least one good friend buffers the negative effects of peer rejection on maladjustment [34,35] and receipt of victimization [36]. However, other work involving an ADHD sample found that only peer rejection, and not friendship, contributed to negative outcomes such as depression 6 and 8 years later [37].…”
Section: Implications Of Peer Problems For Maladjustmentmentioning
confidence: 99%